Level of Patient Satisfaction with the Quality of Health Services at the Rumah Sakit Umum Daerah (RSUD) Cut Meutia, North Aceh Regency - Putri Tia Novita; Kurniawan Kurniawan; Bay Haqi Dalimunthe (International Journal Of Health Science, 2025)
Health centers as primary health care facilities have a strategic role in improving the health of the community. Evaluation of service quality is an important indicator to measure patient satisfaction. The purpose of the study was to determine the level of patient satisfaction with the quality of health services at the Baktiya Health Center, North Aceh Regency. The research method was descriptive quantitative with 237 respondents. The sampling technique used purposive sampling, the instrument was a questionnaire based on the SERVQUAL dimension. The results of the study were that the level of patient satisfaction in the five dimensions showed quite satisfactory results for the tangibles aspect (63%), empathy (63%), assurance (63%), while satisfied with the reliability aspect (57%) and responsiveness (53%). The conclusion is that in general, patients feel quite satisfied with the health services of the Cut Meutia Regional General Hospital (RSUD) in North Aceh Regency.